1996
DOI: 10.1007/bf02890603
|View full text |Cite
|
Sign up to set email alerts
|

Growth and proline accumulation in mungbean seedlings as affected by sodium chloride

Abstract: Mungbean (Vigna radiata L. Wilczek cv. Sujata and cv. K851) seedlings were grown in paper towelins in dark under 0, 0.5, 1, 2 and 3 % (m/v) NaC1 salinity. Germination percentage, shoot and root length, fresh mass of both cultivars decreased with salinity. Total soluble saccharides and proline accumulated in the root and shoot of salt stressed seedlings. The proline accumulation in the root was four to five times higher than that of the shoot of NaCI treated etiolated mungbean seedlings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Mung bean is a salt susceptible (Misra et al, 1996) and Indian mustard is salt tolerant crop (Misra et al, 1995). So it is assumed that their re sponses to salinity might vary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mung bean is a salt susceptible (Misra et al, 1996) and Indian mustard is salt tolerant crop (Misra et al, 1995). So it is assumed that their re sponses to salinity might vary.…”
Section: Resultsmentioning
confidence: 99%
“…Salinity affects growth and metabolism of plants (Misra et al 1995(Misra et al , 1996(Misra et al , 1997a. Chloroplasts are the most sensitive organelles affected by salt stress (Lapina and Popov, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies have also shown that growth is depressed by salinity stress for both common bean (Tejera et al 2005, Gama et al 2007) and mungbean (Misra et al 1996, Sumithra et al 2006, although Bayuelo-Jimenez et al (2002) found considerable variability in salt tolerance when comparing numerous Phaseolus species, and this was especially so in wild types. Further studies are required to investigate potential mechanisms of tolerance to salinity stress in these two crops.…”
Section: Photosynthesis Transpirationmentioning
confidence: 89%
“…Besides, it is well known that free amino acids are important osmolites accumulating in the cells of the different tissues stressed by salt and water, and have been proposed as responsible for salt tolerance (Greenway and Muns 1980, Itoh et al 1987, Kalaji and Pietkiewicz 1993, Schubert et al 1995, Misra et al 1996. AAT inhibition or decrease in AAT expression would be a part of the tissue response to saline stress through free amino acid accumulation.…”
Section: Naci MMmentioning
confidence: 98%